Adult sex ratios and partial dominance of females over males in the rock hyrax - Hemelrijk, Charlotte K.; Seex, Lauren; Pederboni, Matteo; Ilany, Amiyaal; Geffen, Eli; Koren, Lee (Frontiers in Ecology and Evolution, 2022)
Competition in group-living animals often results in a dominance hierarchy. The sex that is larger (usually the males) generally dominates the one that is smaller (the females). In certain species, however, despite being smaller, the females dominate several males. Female dominance over males may here arise from the self-reinforcing effects of winning and losing fights, the so-called winner-loser effect, as demonstrated in the model DomWorld. In the model, females may become dominant over more males when the percentage of males in the group is higher due to the higher intensity of aggression of males than females combined with the higher frequency of male-male fights. This association between female dominance and the percentage of adult males in the group has been confirmed in several primate species. Since in the model DomWorld this association requires few assumptions, it should be tested beyond primates. In the present study, we investigated it in the group-living rock hyrax (Procavia capensis), because it fulfilled most requirements. We used data on adults from six groups, collected over 20 years in natural colonies in Israel. We confirmed that body weight and intensity of aggression was greater in males than females. Three measurements indicated that females dominated ca.70% of the males. Unexpectedly, only in the data where groups comprised several males, female dominance over males was shown to increase with male percentage, but not when including (the many) years in which groups comprised a single male. We attribute this non significance to the limited male-male interactions. One of the requirements of DomWorld is that individuals live in permanent groups, but in rock hyrax there were also bachelor males, that were not permanently associated with a group. Thus, we expected and confirmed that there was no association between the percentage of males and female dominance over males when including them. In conclusion, our results support the hypothesis that the winner-loser effect contributes to the dominance of females over males, and the association between the percentage of males in a group and female dominance over males requires an extra criterion: that most groups contain multiple males.